An analysis on the legality of euthanasia in Nigeria: reforming the law - Salihu, Sani Ibrahim (2018)
Euthanasia is a situation whereby the life of the terminally ill patient is terminated to relieve him from pain and suffering. Studies have shown that euthanasia is common among critical care doctors especially in countries that do not legalize the practice. Meanwhile, countries that legalized euthanasia have the problem of controlling it from being abused. There is a fear that legalizing it will create a slippery slope and no regulation will be able to control it. Euthanasia is illegal in Nigeria. Despite its illegality, this study intends to investigate and find out whether it is being practiced in the country. This research examines the legal framework for the practice of euthanasia in Nigeria. The decision of the Nigerian Supreme Court in MDPDT v. Okonkwo recognized the right of the patient to refuse medical treatment even where it could lead to death, which many scholars regarded this as a starting point for its legalization. This research adopts doctrinal as well as empirical research methodology. Interview method was employed as a compliment to achieve the objectives, thereby making it a sociolegal research. The research selected sixteen respondents for the interview, comprising of major actors in the field of medicine, law, patients and some religious scholars. The research reveals, inter alia, that passive euthanasia, as opposed to active euthanasia, is being practiced in Nigeria. It is therefore discovered that the existing legal framework is inadequate in addressing this issue. Therefore, the recommendation is offered fo the amendment of the existing laws on euthanasia in Nigeria.